2000
DOI: 10.1530/eje.0.1430439
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines suppress leptin release from in vitro differentiated subcutaneous human adipocytes in primary culture via beta1- and beta2-adrenergic receptors

Abstract: Objective: Circulating leptin, the product of the ob gene, is known to be closely correlated with adipose tissue mass, but it is also subject to short-term regulation by a variety of hormones including catecholamines. The aim of this study was to investigate the contribution of the three b-adrenergic receptors to leptin secretion from cultured human adipocytes. Design and methods: The model of in vitro differentiated human subcutaneous adipocytes was used in this study. The presence of the b-adrenoceptor subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 38 publications
3
38
0
2
Order By: Relevance
“…However, in the presence of LPS, propranolol slightly but not significantly decreased LPS-induced leptin release, suggesting that the inhibitory ␤ tone under resting conditions was not present after injection of LPS. Therefore, our data suggest that either circulating epinephrine and͞or norepinephrine or norepinephrine released from noradrenergic terminals may inhibit leptin release by acting on ␤-adrenergic receptors present on cell membranes of the adipocytes (28).…”
Section: Discussionmentioning
confidence: 81%
“…However, in the presence of LPS, propranolol slightly but not significantly decreased LPS-induced leptin release, suggesting that the inhibitory ␤ tone under resting conditions was not present after injection of LPS. Therefore, our data suggest that either circulating epinephrine and͞or norepinephrine or norepinephrine released from noradrenergic terminals may inhibit leptin release by acting on ␤-adrenergic receptors present on cell membranes of the adipocytes (28).…”
Section: Discussionmentioning
confidence: 81%
“…Finally, it has been shown that catecholamines suppress leptin release via b1 and b2 adrenoreceptors. 32,33 Considering the increased lipolysis responsiveness to catecholamines, it cannot be ruled out that a comparable hypersensitivity to catecholamines-induced inhibition of leptin might explain, at least in part, the lower levels of serum leptin concentrations previously observed in subjects born SGA, which in turn might be regarded as an additional deleterious component in the control of insulin sensitivity. 26 Studying the lipolytic response to catecholamines in clearly insulin-resistant subjects born SGA in comparison to insulin-sensitive ones would certainly help to clarify the relationship between these two metabolic abnormalities in this specific clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, concomitant hypoxia attenuated the stimulatory effect of dexamethasone on leptin. A previous study suggested that catecholamines directly inhibit leptin production by binding to adipocyte adrenergic receptors (Scriba et al 2000). It is possible that increased SNS activity in the hypoxic pup blunted the leptin response to dexamethasone.…”
Section: Leptinmentioning
confidence: 96%